The somatic growth pattern of preterm infants until term age - Ida Bagus Andhita; Soetjianingsih Soetjianingsih; I. Wayan Retayasa (Indonesian Pediatric Society, 2009)
Background Pre term infants contribute substantially to neonatalmorbidity and mortality rates. Somatic growth is consideredto be an important indicator of an infant's health status. Themeasurement parameters include body weight (BW), body length(BL), head circumference (HC), and ponderal index (PI). Specificdata on the somatic growth pattern of preterm infants in Indonesiaare unavailable.Objectives To identify the somatic pattern of preterm infantsuntil term age and the influence of gender, nutrition, and nursingmethod on BW, BL, HC, and PI growth during the first week oflife.Methods We recruited premature infants born in Sanglah Hopsital,Denpasar, Bali, and collected data on BW, BL, HC, and PI>All data were presented as mean (SD) and plotted in curves.The relationships among several factors and the somatic growthparameters were analyzed with ANOV A. The level of significancewas set at P < 0.05.Results Among 100 infants, significant differences were detectedin the mean ofBW, BL, HC, and PI, particularly in early preterminfants. Breastfed infants had the highest values with BW 2199grams (SD 198), HC 31.4 em (SD 1.71), and PI 2.48 grams/cm 3(SD 0.36). Infants nursed with the kangaroo method had thehighest values of BW [2450 grams (SD 259)] and BL [48 em(SD 2.34)].Conclusion A significant difference was detected in somaticgrowth according to some parameters, particularly in the earlypreterm infants group. Thus, breast feeding and the kangaroomethod contribute to better somatic growth, and specifically BW.